Improvement of conventional milling process in palm oil processing: rotary filter press - Azmi, Azlin Suhaida; Vengadachalam, Koshela; Jimat, Dzun Noraini (IIUM Press, 2011)
The effectiveness of the Rotary Filter Press in removing solids form the press liquor was examined and then analyzed its possibility in replacing the functions of the conventional screw press and vibrating screen. Literature review on the conventional equipment used in the mill which is Twin Screw Press was conducted. Alternative equipment, the Rotary Filter Press was proposed and its design and principal of operation were discussed. Besides, the advantages and disadvantages of both the conventional and alternative equipment were compared. It was observed that the Rotary Filter Press capable to remove some of the non-oily solids (NOS) from the press liquor but no results were obtained for the feed of Depulper mesh as the fibrous mesh often chocked the system. Therefore, several modifications were suggested to improve the efficiency of the equipment such as control of water dilution in the Depulper mesh and inclusion of perforated plates in the equipment design.